PS 18-11 ESTIMATION OF 24-HOUR URINE SODIUM FROM MULTIPLE SPOT URINE SAMPLES. (September 2016) - Rhee, Moo-Yong; Kim, Ji-Hyun; Shin, Sung-Joon; Gu, Namyi; Nah, Deuk-Young; Kim, Sun-Woong; Park, Ju-Hyun; Kim, Hyun Ja; Oh, Kyung Won
Abstract : Objective: Estimation of 24-hour urine sodium excretion using spot urine (SU) sample has been challenged due to limited accuracy despite of its convenience. We developed equation estimating 24HUNa using average of three SU samples, validated and compared to the equations using single SU sample. Design and Method: Data of morning first, morning and evening SU from 74 individuals were used in the development of equations using average of three SU. The developed equation was validated with data of morning first, daytime and evening SU samples from 174 individuals, and compared to the equations using single SU sample. Results: The equation using average of three SU samples showed the lowest bias of -2.9 mmol/24-h. The equations using single SU sample had bias more than 10 mm/24-h. In the correlation analysis with measured 24HUNa, the ICC of estimated 24HUNa by equation using average of three SU samples was 0.909 and CCC was 0.832. The limits of agreement was -64.1 to 58.3 mmol/24-h for equation using average of three SU samples, but around 100 mmol/24-hr for the equations using single SU sample. Although all the equations showed tendency of over- and under-estimation of 24HUNa depending on the measured 24HUNa, the equation using average of 3 SU samples showed the slope closer to zero among the equations. Conclusions: The equation developed using average of three SU samples showed improved estimation of 24HUNa in population and individual levels compared to the equations using single SU sample.